SYNTHESIS OF LIBERAL AND COMMUNITARIAN PHILOSOPHICAL CONCEPTS IN DISCOURSE ETHICS OF J. HABERMAS - Абисова, М. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article is devoted to the analysis of discourse ethics of J. Habermas as an attempt to overcome the conceptual limitations of liberal and communitarian philosophies in the discussion of the moral bases of modern society.